FAKTOR PENYEBAB PETANI KENTANG LAHAN KERING DATARAN TINGGI KECAMATAN PANGALENGAN, BANDUNG TIDAK MENGADOPSI KONSERVASI TANAH - Ratna Khatarina (Jurnal Ilmu Pertanian Indonesia, 2006)
The main objective of the study is to identify why soil conservation that believed giving more benefits Is not adopted by upland potato’s farmer of pangalengan, Bandung. The study was carried out in pangalengan subdistrict, Bandung. Population of responden is 1148 farmers. Respondent of 180 farmers (15% of population) was drawn randomly from 13 village. The respondent amount of each village was drawn proportionally. The study reveals long term (20 years) and short term (one period of cultivation) impact of three farming systems using an approach of farm income analysis. Two of three farming systems apply soil conservation practices, bench terraces and contour farming systems, while the other does not apply soil conservation practice (slope farming system). Short term of farm income is quantified by using input and revenue prices 2004-2005. Long term of farm income is quantified by using SCUAF (Soil Change Under Agricultural Agroforestry and Forestry) model and Cost Benefit Analysis. In one period of cultivation (short term), farm income of slope farming is higher than farm income of soil consservation practices, benc terraces and contour farming. In 20 years, NPV of bench terraces and contour farming systems is higher than NPV (Net Persent Value) of slope farming system. The long term benefit of soil conservation practices causing farmer reluctant to adopt conservation practices. Soil conservation practices implementation in the future needs supported by policy how to make the long term benefit of conservation is more interesting to farmer such as giving incentive or credit to farmer who adopt soil conservation practice, and as well as the certainty of land holding.